What is the optimal means of preparing the endometrium in frozen–thawed embryo transfer cycles? A systematic review and meta-analysis - Groenewoud, Eva R.; Cantineau, Astrid E.P.; Kollen, Boudewijn J.; Macklon, Nick S.; Cohlen, Ben J. (Human reproduction update, 2013)
BACKGROUND Frozen-thawed embryo transfer (FET) enables surplus embryos derived from IVF or IVF-ICSI treatment to be stored and transferred at a later date. In recent years the number of FET cycles performed has increased due to transferring fewer embryos per transfer and improved laboratory techniques. Currently, there is little consensus on the most effective method of endometrium preparation prior to FET. METHODS Using both MEDLINE and EMBASE database a systematic review and meta-analysis of literature was performed. Case-series, case-control studies and articles in languages other than English, Dutch or Spanish were excluded. Those studies comparing clinical and ongoing pregnancy rates as well as live birth rates in (i) true natural cycle FET (NC-FET) versus modified NC-FET, (ii) NC-FET versus artificial cycle FET (AC-FET), (iii) AC-FET versus artificial with GnRH agonist cycle FET and (iv) NC-FET versus artificial with GnRH agonist cycle FET were included. Forest plots were constructed and relative risks or odds ratios were calculated. RESULTS A total of 43 publications were selected for critical appraisal and 20 articles were included in the final review. For all comparisons, no differences in the clinical pregnancy rate, ongoing pregnancy rate or live birth rate could be found. Based on information provided in the articles no conclusions could be drawn with regard to cancellation rates. CONCLUSIONS Based on the current literature it is not possible to identify one method of endometrium preparation in FET as being more effective than another. Therefore, all of the current methods of endometrial preparation appear to be equally successful in terms of ongoing pregnancy rate. However, in some comparisons predominantly retrospective studies were included leaving these comparisons subject to selection and publication bias. Also patients' preferences as well as cost-efficiency were not addressed in any of the included studies. Therefore, prospective randomized studies addressing these issues are needed.